Magnetic fields produced by 'seen arc' and 'unseen arc' of ideal solenoids are the same in magnitude but opposite in direction. (1st March 2023) - Khalifah, Ardi; Abdullah, Mikrajuddin
Abstract: We divide the solenoid into 'seen arc portion' and 'unseen arc portion' when observed from the point of measurement. The magnitudes of fields produced by the two portions are the same but in opposite directions. This is the reason why the magnetic field outside an ideal solenoid is zero. Interestingly, the magnitude of the field produced by each portion follows the change of angle of view to the outer boundary of the solenoid when observed from the point of measurement. We have also distributed questionaries to students to get feedback on whether the topics discussed in this paper are easy for undergraduate students to understand.